Meningkatkan Hasil Belajar Siswa Dalam Materi Bunyi Pada Mata Pelajaran Ilmu Pengetahun Alam (IPA) Dengan Menggunakan Metode Demonstrasi Pada Siswa Kelas IV SDN Saruni 2 Kecamatan Majasari, Kabupaten Pandeglang, Provinsi Banten - Rifki Arif Nugraha; Siti Nuriah; Ratna Dewi; Ade Farid Hasyim (Desanta Publisher, 2023)
This research is classroom action research (PTK) whose implementation includes four stages, namelyplanning, action, observation and reflection which consists of two cycles where each cycle is carried out intwo meetings. The subjects in the research were class IV students at SDN Saruni 2, Majasari District,Pandeglang Regency, totaling 31 students, consisting of 16 male students and 15 female students. Datacollection instruments use observation sheets and tests. The data analysis technique used is qualitativedescriptive analysis and quantitative descriptive analysis. The success of this research can be seen fromstudent learning outcomes which have increased in cycle I and cycle II. The results of the research show thatthere has been an increase in student learning outcomes in Natural Sciences (Science) subjects using thedemonstration method. The results of student learning completion in cycle I were that out of 31 students therewere 14 students or around 45.15% who had completed their studies and there were 17 students or around 44.85% who had not completed their studies. Meanwhile, in cycle II there was an increase in learningoutcomes, namely there were 29 students or around 93.54% who had completed their studies and there were2 students who had not yet completed their studies or around 6% with the average score of studentsexperiencing an increase in cycles I and cycle II, namely from 66 to 73.87. There were positive changes inattitudes and activities in students during the learning process according to the results of observations duringclassroom actions.